Fast Fashion and its Impact on Environmental Pollution and the Importance of Sustainability in Protecting the Environment (The International Journal for Scientific Research, 2023)
The technological development, globalization, and the change in the purchasing behavior of the consumer lead to the emergence of a production method called rapid fashion, and this method relied on the speed of copying all the designs offered by major international fashion houses and manufacturing them as soon as possible at the lowest cost and provide the latest fashion for the owner in large numbers and at the lowest prices; Cheaply and that method in Production is anti-sustainable, which is mainly based on adherence to the ethics of design, production, environmental conservation and labor rights. The current research aims to focus on scientific research in the field of sustainability, especially in the field of fashion and clothing because of its harmful effects on the environment significantly shedding light on the negative effects of fast fashion. It defines the ethics of sustainability in the field of fashion and its production. And highlight the wrong practices that appear from fast fashion companies. Suggestions must also be made to apply the rules and standards in sustainability in fast fashion. The research problem is determined by the following questions: How effective scientific research is in sustainability in the field of clothing production? What is its impact on the environment? The study followed the analytical approach to analyze the impact of fast fashion and clothing on the environment, and the applied approach in training workers in factories on sustainable methods in the clothing industry by providing ideas and proposals that make the environment clean for sustainability and applying them in the field of clothing. And conducting interviews for experts and decision makers in ready-made clothing factories and companies to poll their opinions through a scale to find out whether sustainability in clothing and the use of trust materials have an impact on the environment towards the proposed study and reach the results. The results of the study found a statistically significant relationship between sustainability in the field of clothing and consumer and environmental preservation by 83% and an average correlation of 8.51. There is also a statistically significant relationship between workers in the manufacture of clothing and maintaining sustainability standards to protect the environment between sustainability 73% with an average correlation of 0.49. With a significance level of 0.00. The researcher recommends paying attention to scientific studies that are concerned with the areas of sustainability to preserve the environment and consumer awareness in the field of sustainability and environmental preservation.
Keywords: Fast Fashion; Sustainability; Environment